Anxiety disorders and the gut microbiota: a bibliometric and visual analysis - Linli Guo; Linli Guo; Qin Ding; Qin Ding; Qing Li; Danping Zheng; Danping Zheng; Linglin Guo; Linglin Guo; Xiaotao Cao; Xiaotao Cao; Qianqian Mou; et al. (Frontiers in Psychiatry)
IntroductionAnxiety disorder is a common mental illness, yet its specific mechanisms remain unclear. Recent research has revealed a connection between gut microbiota and anxiety disorders. This study aims to assess the current global research landscape, highlight current topics of interest, and explore future research directions in the field of anxiety disorders and gut microbiota.MethodsWe extracted research review articles related to anxiety and gut microbiota from the Web of Science, covering the period from 2004 to 2023. We used VOSviewer 1.6.18.0, Scimago Graphica, and CiteSpace 6.2. R2 to visualize the contributions of countries, institutions, journals, authors, citations, and keywords in this field.ResultA total of 1198 articles were included in this bibliometric analysis. Over the past two decades, both publications and citations have shown a steady increase. China, the United States, and Canada were the top three countries in terms of publication output. John Cryan from University College Cork had the highest number of publications and citation impact in this area of research. The journal Nutrients had the highest number of publications, while Brain Behavior and Immunity had the most citations. Key research themes in recent years have included anxiety, gut microbiota, depression, stress, gut-brain axis, and probiotics, all of which are likely to be important future research directions.ConclusionThis analysis has key research areas and emerging trends, including risk factors, stressors, inflammatory responses, the gut-brain axis, and probiotics. These insights can guide researchers towards a more comprehensive understanding of recent advancements in this field, help shape future research directions and facilitate the identification of new therapeutic targets for anxiety disorder, ultimately improving clinical outcomes.